Real-Time RF Energy Harvesting System with Software Defined Radio - Ozkan, Lütfullah; Büyükçorak, Saliha; Kurt, Günes Karabulut (IEEE, 2023)
The number/variety of electronic devices and energy requirements increase in next-generation communication systems (5G+) with the incredible increase in user demands and the rapid development of the technology. Simultaneous wireless information and power transfer (SWIPT) and radio frequency energy harvesting (RF-EH) technologies reveal great potential to meet these needs. Motivated by this, this paper presents a software defined radio (SDR) based real-time RF-EH system that studies the harvested energy efficiency subject to average battery charging time (BCT) and average received signal strength indicator (RSSI) parameters. Via real-time measurements, the effects of modulation type, antenna number and carrier frequency variation on BCT and RSSI parameters have been investigated for different transmitter/receiver distances.
31st IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUL 05-08, 2023 -- Istanbul Tech Univ, Ayazaga Campus, Istanbul, TURKEY
Keywords: RF energy harvesting; software defined radio; battery charge time; received signal strength indicator